Intravenous to Oral Switch in Complicated Staphylococcus aureus Bacteremia Without Endovascular Infection: A Retrospective Single-Center Cohort Study. (19th February 2021) - Kouijzer, Ilse J E; van Leerdam, Eline J; Gompelman, Michelle; Tuinte, Renee A M; Aarntzen, Erik H J G; Berrevoets, Marvin A H; Maat, Ianthe; Bleeker-Rovers, Chantal P; van Crevel, Reinout; ten Oever, Jaap
Abstract: In this retrospective cohort study, selected patients with disseminated Staphylococcus aureus bacteremia, but without endovascular infection on echocardiography and 18 F-FDG-PET/CT, were free of relapse after IV-oral switch. Mortality was low and similar to patients who received prolonged intravenous treatment. IV-oral switch was associated with a shorter length of hospital stay.